Propagación in situ del banano maqueño red dacca (mussa acuminata) utilizando bencil amino purina (BAP) y ácido indolacético (AIA) - Moncayo Onofre, Pablo Vicente (2022)
Among the main limitations of banana cultivation and its numerous varieties of commercial interest, among which Red Dacca stands out, is the scarce availability of planting material for the producer. For this reason, the present research was developed, which evaluated the in situ propagation of this material using Benzyl Amino Purine (BAP) and Indoleacetic Acid (IAA). For this purpose, an experimental plot was established in the rural parish of "La Guayas" in the canton of El Empalme, in the north of the province of Guayas. For the statistical analysis, a completely randomized block design (CRBD) was used, consisting of four treatments (T0, T1, T2 and T3) and four replications, while the Tukey test (p≤ 0.05) was used for the comparison of means. The variables evaluated were: number of shoots, shoot length (cm), shoot diameter (cm), shoot vigor (%), survival (%) and economic analysis. In relation to the results obtained, statistical equality between treatments was evidenced in each of the variables mentioned above (p¬>0.05); however, it is important to highlight that numerically the highest registers were reached by T2 (40 mg/L of BAP + 12 mg/L of AIA), which resulted in a greater number of shoots and therefore greater profitability in the economic analysis with 776.77%, followed by T0 and T3 with 657.98 and 624.57%, while T1 presented 422.27%. Finally, it is concluded that, although the use of BAP and AIA does not induce the exponential sprouting of Red Dacca banana shoots, the effect generated at concentrations of 40 mg/L of BAP + 12 mg/L of AIA would improve the producer's profits.